COMPARATIVE EVALUATION OF THE EFFECT OF DIFFERENT ROTARY INSTRUMENT SYSTEMS ON THE AMOUNT OF APICALLY EXTRUDED DEBRIS - Bilge Lenger; Recai Zan (Cumhuriyet University, 2022)
Objectives: The purpose of our study is to examine in vitro the amount of debris extrusion from the apical after root canal preparation with different rotary instruments. Materials and Methods: In present study, 60 single root single-canal lower premolar human teeth were used. The teeth were randomly selected and divided into 4 main groups (n=15). Root canals are shaped by using 2Shape, One Curve and XP-3DEndo Shaper working in rotational motion and WaveOne Gold working reciprocal motion. Later, the weight of each eppendorf tube was weighed on a precision scale and the amount of debris extrusion from the apical was determined with 10ˉ4 precision by subtracting the empty weight of the tube. Since the parametric test assumptions were fulfilled in the evaluation of the data obtained regarding the amount of debris extrusion from the apical of file systems by loading them into the SPSS 22.0 program, One-Way Variance analysis was used and the level of error was taken as 0.05. Results: When the amount of debris extrusion from the apical is ordered from high to low, it was seen that there are 2Shape, One Curve, XP-Endo Shaper, WaveOne Gold. However, the difference between study groups was not statistically significant (p> 0.05). Conclusions: Considering the results obtained in terms of debris extrusion from the apical about the new generation files with different metallurgy, kinematics, structural features, designs and different configurations that we used ın present study, it was seen that these systems would not show any difference in terms of the effect of debris on the success of endodontic treatment.